Study Of Community's Perception Level Malahing On The Development Of Tourism Potential In The Kampung Malahing, Village Tanjung Laut Indah, Bontang Selatan District, Bontang City East Kalimantan Province - Andy Suardysapar; Helminuddin; Iwan Suyatna (2339-1324, 2022)
The purpose of this study was to determine the level of perception of the Malahing community towards the development of tourism potential in Malahing Village, Tanjung Laut Indah Village, Bontang Selatan District, Bontang City. The research phase began in September 2019 and the final examination was carried out in December 2020. Sampling used the quouta sampling method, which is to gather information from a number of certain people (15 respondents) who are considered to be able to provide responses (their perceptions) about tourism development in Malahing Village. The method using the Likert scale is used to reveal respondents' perceptions about the discourse of developing the tourism potential of Malahing Village. The results showed the level of perception of the Malahing community towards the development of tourism potential in Malahing Village cumulatively with a high category with a score of 20.2 which was in the class interval 16.36 - 21.00, meaning that the community was very supportive of developing tourism potential in Malahing Village, Tanjung Village. Laut Indah, South Bontang District, Bontang City Keywords: Tourism potential, Malahing village